2011
DOI: 10.1007/s11663-011-9542-1
|View full text |Cite
|
Sign up to set email alerts
|

Grain Floatation During Equiaxed Solidification of an Al-Cu Alloy in a Side-Cooled Cavity: Part II—Numerical Studies

Abstract: In this article, a single-phase, one-domain macroscopic model is developed for studying binary alloy solidification with moving equiaxed solid phase, along with the associated transport phenomena. In this model, issues such as thermosolutal convection, motion of solid phase relative to liquid and viscosity variations of the solid-liquid mixture with solid fraction in the mobile zone are taken into account. Using the model, the associated transport phenomena during solidification of Al-Cu alloys in a rectangula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Wu's simulation study did not take account of the movement of equiaxed grains, which can markedly influence the solidification structure of castings. 22,23) Also, the solidification structure refinement of Al-Cu alloys in super-gravity field has been investigated systematically in our recent study, 24) which demonstrated that the "crystal rain" caused by super-gravity contributed to the grain refinement.…”
Section: Effect Of Super-gravity Field On Grain Refinement and Tensilmentioning
confidence: 96%
“…Wu's simulation study did not take account of the movement of equiaxed grains, which can markedly influence the solidification structure of castings. 22,23) Also, the solidification structure refinement of Al-Cu alloys in super-gravity field has been investigated systematically in our recent study, 24) which demonstrated that the "crystal rain" caused by super-gravity contributed to the grain refinement.…”
Section: Effect Of Super-gravity Field On Grain Refinement and Tensilmentioning
confidence: 96%
“…When super gravity is applied throughout the solidification process, the crystals collect in the middle of the sample, shown in Figure 7d. In a normal gravity field, the crystals also settle [25,35,36]. In our experimental result shown in Figure 7e, the solidification structure at the bottom area is obviously finer than that at the top of the sample, a difference caused by the settling of the crystals.…”
Section: Discussionmentioning
confidence: 85%
“…Hence the crystals cause the FGZ at the bottom of the sample, as shown in Figure 7 b. With further treatment, ending when the solid fraction reaches 80 wt %, the crystals reverse direction and began to move upward within the sample, gathering in the middle of the sample as shown in Figure 7 c. When super gravity is applied throughout the solidification process, the crystals collect in the middle of the sample, shown in Figure 7 d. In a normal gravity field, the crystals also settle [ 25 , 35 , 36 ]. In our experimental result shown in Figure 7 e, the solidification structure at the bottom area is obviously finer than that at the top of the sample, a difference caused by the settling of the crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1: The mushy zone is a mixture of solid and liquid that leads to a reduced fluid flow (adapted from [6]).…”
Section: Introductionmentioning
confidence: 99%